1992
DOI: 10.1139/m92-048
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of chymotrypsin as a sole carbon and (or) nitrogen source by Escherichia coli

Abstract: alpha-Chymotrypsin serves as a sole carbon source, sole nitrogen source, and as sole carbon plus nitrogen source for wild-type Escherichia coli in a totally defined medium. Hence, a mammalian host for E. coli may supply the necessary carbon and nitrogen nutrients for the microorganism. Growth is most rapid when chymotrypsin is a sole nitrogen source and least rapid with chymotrypsin as a carbon source. The approximate doubling times for E. coli utilizing chymotrypsin as a nitrogen source, carbon plus nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…2). Similar results were reported by Brecher et al (1992) concerning the growth of E. coli on degradation products of chymotrypsin, where the peptides support growth most effectively as the nitrogen source and less as the carbon source. Utilization of peptides by C. glutarnicum did occur even if lysine, which cannot be metabolized (Nakayama, 1985), was present in the peptide.…”
Section: Discussionsupporting
confidence: 86%
“…2). Similar results were reported by Brecher et al (1992) concerning the growth of E. coli on degradation products of chymotrypsin, where the peptides support growth most effectively as the nitrogen source and less as the carbon source. Utilization of peptides by C. glutarnicum did occur even if lysine, which cannot be metabolized (Nakayama, 1985), was present in the peptide.…”
Section: Discussionsupporting
confidence: 86%
“…coli cannot use native proteins, Brecher et al (1992) showed that this species may use peptides as a C or N source under C-limited conditions. The rumen of animals in temperate climates is not usually N-limited and therefore, the addition of an N source to rumen fluid does not influence the growth of E. coli in rumen fluid (Duncan et al 1999a).…”
Section: The Effect Of Ruminant Production Diets On Survival Of E Colimentioning
confidence: 99%